What influences a teacher's decision to leave or remain in teaching? A case of Dr. John Garang Memorial and Juba Day Secondary Schools in Juba County Central Equatoria State, Republic of South Sudan - Manyok Ajak, Mading (My University, 2015)
This study is primarily aimed at finding out the root causes of teacher attrition (teacher dropout) in the conflict affected South Sudan, Central Equatoria State. A case study was conducted in two secondary schools and the national Ministry of Education Science and Technology, in Juba County, Central Equatoria State. Data were collected qualitatively using unstructured interviews and analysis of related documents. It is a common knowledge in the Republic of South Sudan that since the signing of the Comprehensive Peace Agreement (CPA) in 2005, the Government of South Sudan and its educational providers have been recruiting and employing teachers at different levels of education: early childhood, primary education and secondary education. However, a severe shortage of qualified teachers exists in schools and the question that keeps on arising is: what is the cause of teachers’ departure from teaching? Perhaps, the movement of teachers out of the teaching profession could be attributed to the fact that, working environments in schools are no longer friendly to teachers: salaries are low, training opportunities are rare and teaching is being viewed as a profession of low income and prestige. Moreover, it is apparent in most South Sudanese urban secondary schools that class sizes are large, teaching workload is huge and unrewarded, cost of living is high, accommodation for teachers is problematic, professional development programs are unheard of, and cases of physical insecurity in remote rural area schools are prevalent (MoEST-EMIS, 2009). It should therefore be acknowledged that although there are teachers committed to teaching as a profession, it is equally feared that they might succumb to these harsh conditions and the education Millennium Development Goals (MDG) would not be achieved in the near future if the current rate of teacher attrition in the Republic of South Sudan continues. This study was therefore conducted in response to the loss of teachers and has two key objectives. The first is to explore the problem of teacher attrition in the conflict affected \South Sudanese secondary schools in Central Equatoria State, and the second is to suggest possible ways for reducing the problem of teacher attrition. The study concludes that teacher attrition and retention are influenced by the interplay of practices, processes and factors that mediate a teacher’s decision towards teaching as a profession. The study recommends that in order for the Government and educational providers to reduce the problem of teacher attrition in secondary schools, they should address the issues of teacher salary, incentives, class size, school material supplies, learning facilities, teacher recruitment, teacher training, teacher accommodation, transport, and encourage effective links between teachers and communities.
A Thesis submitted to the School of Education, University of the Witwatersrand, Johannesburg South Africa, in partial fulfillment of the requirements of the Degree of Master of Education. Johannesburg, 2015